The Effects of Soaking Treatments and Fermentation Process on Nutritional and Aflatoxin Contents of Fermented Peanut Cake (Black Oncom) - Rohimah, Azizah; Setiawan, Budi; Roosita, Katrin; Palupi, Eny (Polish Journal of Natural Sciences, 2023)
The existing product of fermented peanut cake, namely black oncom as a traditional food of West Java contains high aflatoxin and less nutritional contents. This study aimed to evaluate the adaptive processing method using the effect of soaking treatment and fermentation process on nutritional and aflatoxin contents of black oncom. Parameters evaluated in this study were the fermentation quality (pH and mold density), nutritional contents (water, ash, protein, lipid, carbohydrate, crude fiber, dietary fiber, and protein digestibility) and aflatoxin (aflatoxin B1 and total aflatoxin). These parameters were evaluated for peanut cake with unfermented condition and fermented condition such as commercial black oncom as a traditional (natural) fermentation and the adaptive processing method of black oncom with three soaking treatments of peanut cake, i.e., water (BW), acetic acid 5% (BA) and chitosan 5% w/v (BC) and the use of yeast starter of Rhizopus oligosporus. The results showed that growth of mold were spread more homogeneously in BW compared to BC and BA. The adaptive procedure of BW treatment produced black oncom with better nutritional value (crude fat 37.46% and protein digestibility 77.91%) and lower aflatoxin content within acceptable level of regulatory standard than the commercial black oncom in the market. In conclusion, the adaptive fermentation of black oncom processing which used water treatment and the use of yeast starter of Rhizopus oligosporus might be applied as a potential solution for black oncom production with better nutritional value and acceptable aflatoxin content.